JUSTIFICATION OF OPTIMUM PARAMETERS AND MATHEMATICAL MODEL OF HIGH-TEMPERATURE ROTATIONAL STERILIZATION OF COMPOTES IN SKO-1- 82-3000 CONTAINER - M. E. Achmedov; A. F. Demirova; N. G. Zagirov; V. V. Pinyaskin; M. M. Achmedova (Вестник Дагестанского государственного технического университета: Технические науки)
Researches for clarification of influence of temperature and speed of heated air on dynamics and duration of process of heating of compotes in SKO 1-82-3000 container are conducted. Researches are conducted at speeds of heated air from 1,2 m/s to 8,5m/s and temperatures 120-1500C.It is revealed that for SKO 1-82-3000 banks it is possible to consider as the optimum temperature of the heat carrier (heated air) tv =150 and higher than 0C. The analysis of experimental data and their processing with use of a method of the smallest squares allowed to receive the equation for calculation of duration of heating of compotes in a stream of heated air in SKO 1-82-3000 container depending on temperature of the heating tv environment and its speed υв .The relative error by comparison of settlement and skilled data fluctuates within 5–8%